2022
DOI: 10.3390/ijerph19020881
|View full text |Cite
|
Sign up to set email alerts
|

Elite Triathlete Profiles in Draft-Legal Triathlons as a Basis for Talent Identification

Abstract: Draft-legal triathlons are the main short-distance races worldwide and are those on which talent-identification programs are usually focused. Performance in these races depends on multiple factors; however, many investigations do not focus on elite triathletes. Therefore, the aim of this narrative review was to carry out a systematic literature search to define the elite female and male triathlete profiles and their competition demands in draft-legal triathlons. This will allow us to summarize the main determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 80 publications
(203 reference statements)
3
7
0
Order By: Relevance
“…The anthropometric characteristics of the women studied were similar to the values presented by other authors [ 51 , 52 , 53 , 54 ]. Most of the studies that have analysed data from elite triathletes have focused mainly on the athletes’ height, body weight, and body fat levels expressed as percentage body fat or total body skinfolds.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The anthropometric characteristics of the women studied were similar to the values presented by other authors [ 51 , 52 , 53 , 54 ]. Most of the studies that have analysed data from elite triathletes have focused mainly on the athletes’ height, body weight, and body fat levels expressed as percentage body fat or total body skinfolds.…”
Section: Discussionsupporting
confidence: 85%
“…Most of the studies that have analysed data from elite triathletes have focused mainly on the athletes’ height, body weight, and body fat levels expressed as percentage body fat or total body skinfolds. Elite triathletes tend to have about 7–12% more body fat than those men taking up this type of sport [ 51 , 52 ]. The average height of female athletes has remained around 167 cm over the years, but a decrease in body weight has been noted, from around 60 kg at the beginning of the century to around 55 kg now.…”
Section: Discussionmentioning
confidence: 99%
“…For all these reasons, different causes have traditionally been shown that made it difficult for women to reach high running rhythms, with the planning being carried out with a generic design and without taking their physiological or hormonal considerations into account, compared to those of men [ 30 ]. The fact that no significant differences were found in the rest of the parameters is related to the fact that, although the level is amateur, they are triathletes who compete regularly, and their energy systems are developed and stimulated to perform intense training [ 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caro [ 42 ] stated that the fatigue generated by swimming and cycling makes the arms swing less. In turn, the fatigue in the hamstring muscles generated in the cycling segment makes the support time longer and flight phase more less accentuated [ 32 , 43 ]. In line with the findings found, Coles et al [ 44 ] determined that, in cycling situations where drafting is not allowed, oxygen consumption increases between 18–33% and lactate accumulation appears earlier than it does on circuits without drafting.…”
Section: Discussionmentioning
confidence: 99%
“…In athletics, peak performance age would be between 25 and 27 years in 5000 m and 10 000 m track events, and between 28 and 29 years in marathon distance 3 . In short‐distance triathlon, some studies indicate that peak performance is reached at around 27 years in both males and females 4,5 . These data reinforce the fact that systematic training over several seasons is needed to compete at the highest level in any endurance sport.…”
Section: Introductionmentioning
confidence: 89%